PERHITUNGAN VALUE AT RISK (VaR) DENGAN METODE HISTORIS DAN MONTE CARLO PADA SAHAM SUB SEKTOR ROKOK - Achmad Dimas; Muhammad Azhari; Khairunnisa Khairunnisa (Jurnal Riset Bisnis dan Manajemen, 2018)
The government’s policy, the Indonesian Ulema Council’s (MUI) fatwa, the rise of cigarette issues and anti-smoking campaigns have been a major challenge for the tobacco industry in managing risks. Through this research, the issues will be measured by VaR to know the risk of the company’s shares of cigarette sub sector by using time series data and analyzed by using the simulation method of Historis and Monte Carlo. The results showed the VaR value of GGRM and HMSP stock with the historical method is 3.28 and 2.54%. While the value of VaR shares GGRM and HMSP with Monte Carlo method is 3.52% and 3.14%. Monte Carlo simulation gives greater result than Historical Simulation, because Monte Carlo simulation do iteration repeatedly by involving random number generation and many synthesize the data so that sample data becomes more which makes the calculation is bigger.